The Role of HR Analytics, Entrepreneurial Orientation and Green Innovation in enhancing Organization Performance: Evidence from PLSSEM Framework - Muhammad Asif Qureshi, Muhammad Shujaat Mabarik, Shafiq UR Rehman Massan, Samiullah Sohu, Mehran Khan Tunio (International Journal of Advanced Science and Technology, 2020)
The present world has observed numerous adverse effects of worsening environmental conditions thatare harmful to businesses, natural habitat, and future human survival. Following this statement, thecurrent study aims to identify the relationship between green innovation, HR analytics,entrepreneurial orientation, and organizational performance. In particular, the present study seeks toexplore the potentials of evidence-based analytics of people and business operations in drivingorganizational performance along with the relevant contribution of green product innovation, greenprocess innovation, and entrepreneurial orientation. The results of PLS-SEM confirm that greeninnovation, HR analytics,and organizational performance have positively and significantlyinfluencedby entrepreneurial orientation. The results of partial least square equation modelling displayinglikewise demonstrate that HR analytics have a positive and significant impact on organizationalperformance. Moreover, the results further indicate that green innovationalso hasa positive andsignificantimpact on organizational performance in different multinational firms in Malaysia.Insimple, the results of partial least square modellingconfirm that all three components, i.e.,organizational performance, green innovation, and HR analytics are significantly influenced byentrepreneurial orientation.Moreover, the results suggested that HR analytics and green innovationarea significant contributor to enhancing the performance of multinational firms in Malaysia.